PENGEMBANGAN ASESMEN FORMATIF DISERTAI FEEDBACK UNTUK MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Ana Khoirunnisak; Ari Abi Aufa; Ahmad Shofiyuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Formative assessment enhances students' potential and achievement by evaluating their learning outcomes. It helps determine whether the learning material needs to be revisited based on assessment results. Formative assessment is conducted during the learning process to provide continuous feedback to students. Its goal is to monitor students' progress, identify strengths and weaknesses, and offering appropriate guidance to improve learning. This Research and Development study employed the ADDIE model, which includes the Analysis, Design, Development, Implementation, and Evaluation phases. Data collection methods used in this research included observation, questionnaires, interviews, and tests. The respondents consisted of material experts, assessment experts, educators, and students. The techniques employed were descriptive qualitative, descriptive quantitative, and Rasch model analysis. Validation results from material and assessment experts showed that the content aspect had an average score of 83.3% (very valid), the constructed aspect scored 87.5% (very valid), and the appearance aspect scored 75% (valid). The practicality aspect achieved an average score of 97.5% (very valid). The questionnaire results from material experts, assessment experts, educators, and students indicated that the readability aspect received an average score of 93% (very valid). Based on these results, it can be concluded that the formative assessment developed meets the criteria for validity. The Rasch model analysis also indicated that all 20 items met the criteria for item reliability, person reliability, and Cronbach's alpha, concluding that the formative assessment developed is reliable.